Caractérisation de couches minces élaborées par la méthode spray destinées à des applications photovoltaïques - Imène NAOUI (My University, 2025)
In this work, we present the deposition of four semiconductor metal oxides films for photovoltaic applications using the Spray Pyrolysis method. Theoretical and practical aspects of the Spray method used, as well as the different thin film deposition and characterization techniques, are discussed. The deposited oxides films are zinc oxide (ZnO), copper oxide (CuO), iron oxide (Fe₂O₃), and tin oxide (SnO₂). The crystallinity of the deposited films was verified by X-ray diffraction, and optical gaps were measured using transmittance measurements. The characterization results for the four oxides are consistent with the literature. --------------------------------------------------------------------------- في هذا البحث ، نقدم ترسيب أربعة أكاسيد معدنية شبه موصلة على شكل أغشية رقيقة لتطبيقات الطاقة الكهروضوئية باستخدام طريقة التحلل الحراري بالرش . يناقش البحث الجوانب النظرية والعملية المتعلقة بطريقة الرش المستخدمة بالاضافة الى التقنيات المختلفة لتطوير وتوصيف الاغشية الرقيقة . الأكاسيد المرسبة هي أكسيد الزنك ، وأكسيد النحاس ، وأكسيد الحديد ، وأكسيد القصدير ، تم التحقق من تبلور الأغشية المترسبة باستخدام حيود الأشعة السينية ، وقيست الفجوات الضوئية باستخدام قياسات النفاذية ، تتوافق نتائج توصيف الأكاسيد الأربعة مع ماهو مذكور في الأبحاث العلمية . --------------------------------------------------------------------------- In this work, we present the deposition of four semiconductor metal oxides films for photovoltaic applications using the Spray Pyrolysis method. Theoretical and practical aspects of the Spray method used, as well as the different thin film deposition and characterization techniques, are discussed. The deposited oxides films are zinc oxide (ZnO), copper oxide (CuO), iron oxide (Fe₂O₃), and tin oxide (SnO₂). The crystallinity of the deposited films was verified by X-ray diffraction, and optical gaps were measured using transmittance measurements. The characterization results for the four oxides are consistent with the literature.
Keywords: : thin film spray pyrolyse optical charateriwation structural characterization.; الاغشية الرقيقة التحلل الحراري بالرش التوصيف الضوئي التوصيف البنيوي; Couches minces Spray pyrolyse caractérisation optique caractérisation structurelle